PERSEPSI MASYARAKAT DESA KESUGIHAN KIDUL KECAMATAN KESUGIHAN TERHADAP PROFESI ADVOKAT - Fitri, Eka Nur (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
As the era develops in the rule of law, there are many problems in society and officials, there is a lot of legal uncertainty regarding justice. Law enforcement in a society depends on the good and bad of the legal professionals who carry out their profession. The research uses field research which produces descriptive data, which is observed about people or behavior in the form of written/spoken words directly into the field. From the results of research on the views of the people of Kesugihan Kidul Village towards the Advocate Profession, only highly educated people understand the duties and functions of Advocates and the community considers that the Advocate Profession sometimes has pros and cons, there are some people who think that advocates only defend the poor, so the people of Kesugihan Kidul Village rarely use it. Advocate services and supported by economic factors, knowledge factors, experience factors. The public hopes that advocates provide legal education and legal counseling services so that there is no opposition to the profession of advocates for their professionalism and quality as law enforcers.